To solve the expression
\[ -\frac{3}{15} - \frac{2}{5} - \frac{15}{3} - \frac{5}{2}, \]
let's simplify each term first.
Step 1: Simplifying the fractions
-
\(-\frac{3}{15}\): \[ -\frac{3}{15} = -\frac{1}{5} \quad (\text{since } 3 \div 3 = 1 \text{ and } 15 \div 3 = 5) \]
-
\(-\frac{2}{5}\): \[ -\frac{2}{5} \text{ is already in its simplest form.} \]
-
\(-\frac{15}{3}\): \[ -\frac{15}{3} = -5 \quad (\text{since } 15 \div 3 = 5) \]
-
\(-\frac{5}{2}\): \[ -\frac{5}{2} \text{ is already in its simplest form.} \]
Step 2: Rewrite the expression
Now we can rewrite the entire expression substituting the simplified forms:
\[ -\frac{1}{5} - \frac{2}{5} - 5 - \frac{5}{2}. \]
Step 3: Combining \(-\frac{1}{5}\) and \(-\frac{2}{5}\)
\[ -\frac{1}{5} - \frac{2}{5} = -\frac{1 + 2}{5} = -\frac{3}{5}. \]
Now the expression is: \[ -\frac{3}{5} - 5 - \frac{5}{2}. \]
Step 4: Getting a common denominator
To combine \(-5\) and \(-\frac{5}{2}\), we convert \(-5\) to a fraction with a denominator of 2: \[ -5 = -\frac{10}{2}. \]
Now we have: \[ -\frac{3}{5} - \frac{10}{2} - \frac{5}{2}. \]
Combining \(-\frac{10}{2}\) and \(-\frac{5}{2}\): \[ -\frac{10}{2} - \frac{5}{2} = -\frac{10 + 5}{2} = -\frac{15}{2}. \]
Step 5: Combine remaining terms
Now we have: \[ -\frac{3}{5} - \frac{15}{2}. \]
Step 6: Getting a common denominator for \(-\frac{3}{5}\) and \(-\frac{15}{2}\)
The common denominator of 5 and 2 is 10. We convert each fraction:
-
\(-\frac{3}{5}\): \[ -\frac{3}{5} = -\frac{3 \times 2}{5 \times 2} = -\frac{6}{10}. \]
-
\(-\frac{15}{2}\): \[ -\frac{15}{2} = -\frac{15 \times 5}{2 \times 5} = -\frac{75}{10}. \]
Step 7: Combine the fractions
Now combining \(-\frac{6}{10}\) and \(-\frac{75}{10}\): \[ -\frac{6}{10} - \frac{75}{10} = -\frac{6 + 75}{10} = -\frac{81}{10}. \]
Final Answer
So, the simplified result of the original expression is:
\[ \boxed{-\frac{81}{10}}. \]